Proceedings of the 12th International Workshop on Semantic Evaluation 2018
DOI: 10.18653/v1/s18-1039
|View full text |Cite
|
Sign up to set email alerts
|

PlusEmo2Vec at SemEval-2018 Task 1: Exploiting emotion knowledge from emoji and #hashtags

Abstract: This paper describes our system that has been submitted to SemEval-2018 Task 1: Affect in Tweets (AIT) to solve five subtasks. We focus on modeling both sentence and word level representations of emotion inside texts through large distantly labeled corpora with emojis and hashtags. We transfer the emotional knowledge by exploiting neural network models as feature extractors and use these representations for traditional machine learning models such as support vector regression (SVR) and logistic regression to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…The second place winner of the SemEval leaderboard trained a word-level bidirectional LSTM with attention, and it also included non-deep learning features in its ensemble [34]. Ji Ho Park et al [35] trained two models to solve this problem: regularized linear regression and logistic regression classifier chain [11]. They tried to exploit labels' correlation to perform multi-label classification.…”
Section: Emotion Classification In Tweetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second place winner of the SemEval leaderboard trained a word-level bidirectional LSTM with attention, and it also included non-deep learning features in its ensemble [34]. Ji Ho Park et al [35] trained two models to solve this problem: regularized linear regression and logistic regression classifier chain [11]. They tried to exploit labels' correlation to perform multi-label classification.…”
Section: Emotion Classification In Tweetsmentioning
confidence: 99%
“…• NTUA-SLP: the system submitted by the winner team of the SemEval-2018 Task1:E-cchallenge[33].• TCS: the system submitted by the second place winner[34]. • PlusEmo2Vec: the system submitted by the third place winner[35].•Transformer: a deep learning system based on large pre-trained language models developed by the NVIDIA AI lab[39].…”
mentioning
confidence: 99%
“…ethos). Instances derived from research on emoji hashtags showed that Twitter and Instagram users tag a cluster of emoji to convey a message subject [18] and to express emotional statement [32].…”
Section: Emoji Sequencesmentioning
confidence: 99%
“…Ensemble methods have been shown very effective in many natural language processing tasks (Park et al, 2018;Winata et al, 2019). We apply an ensemble method by taking the top five translations from word-level and subword-level NMT, and rescore all translations using our pre-trained Czech language model mentioned in §2.3.…”
Section: Model Ensemblementioning
confidence: 99%